Evaluating the Impact of Hybrid Workforce Models in Healthcare Administration on Hospital Efficiency and Staff Satisfaction - Alharithy, Mr. Mohammad Abdulah Abdullah; Alnasiri, Mr. Bandar Abed Abdullah; Alnasiri, Mr. Khalaf Abed Abdullah; Alsalmy, Mr. Hamed Madah Awad; Alamri, Mr. Mohsen mohammad; aljohani, Mr. Sattam hamoud hammad; Waleed Abdulrahman Abdulhamid Banjar, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study explores the transformative potential of hybrid workforce models in healthcare administration, focusing on their impact on hospital efficiency and staff satisfaction. Hybrid models, which integrate remote and in-person work, offer significant flexibility and innovation. However, they pose unique challenges, such as technology gaps and resistance to change. A cross-sectional study conducted with healthcare professionals across Saudi Arabia highlights the operational benefits of these models, such as improved resource allocation and enhanced staff satisfaction. Nonetheless, barriers such as insufficient infrastructure must be addressed to fully realize their potential. Recommendations include targeted training, investments in technology, and the establishment of unified policies to enhance hybrid workforce adoption in healthcare.